Structure and Photocatalytic Properties of TiO2-WO3 Composites Prepared by Electrophoretic Deposition. Issue 1 (9th March 2015) - Liepina, Ineta; Bajars, Gunars; Rublans, Marcis; Kleperis, Janis; Lusis, Andrejs; Pentjuss, Evalds
Abstract: In this work TiO2 -WO3 composite films containing different oxide concentrations were prepared by electrophoretic deposition on steel substrates. Composite coating structures were analyzed by X -ray diffraction, Raman spectra and scanning electron microscopy. The results showed an even distribution of WO3 particles in the entire composite layer. Light absorption measurements were used for photocatalytic properties evaluation. It was found that the removal ratio of methylene blue depends on the (TiO2 ):(WO3 ) concentration ratio. The most effective photodegradation was determined for the sample that was electrophoretically deposited from the suspension with the molar content ratio n(TiO2 ):n(WO3 ) 2:1.